2, 2, 2‐trifluoroacetophenone‐based D‐π‐A type photoinitiators for radical and cationic photopolymerizations under near‐UV and visible LEDs. Issue 13 (5th February 2016) - Jin, Ming; Yu, Man; Zhang, Yuan; Wan, Decheng; Pu, Hongting
ABSTRACT: Two D‐π‐A‐type 2, 2, 2‐trifluoroacetophenone derivatives, namely, 4′‐(4‐( N, N ‐diphenyl)amino‐phenyl)‐phenyl‐2, 2, 2‐trifluoroacetophenone (PI‐Ben) and 4′‐(4‐(7‐( N, N ‐diphenylamino)‐9, 9‐dimethyl‐ 9H ‐fluoren‐2‐yl)‐phenyl‐2, 2, 2‐trifluoroacetophenone (PI‐Flu), are developed as high‐performance photoinitiators combined with an amine or an iodonium salt for both the free‐radical polymerization of acrylates and the cationic polymerization of epoxides and vinyl ether upon exposure to near‐UV and visible light‐emitting diodes (LEDs; e.g., 365, 385, 405, and 450 nm). The photochemical mechanisms are investigated by UV‐Vis spectra, molecular‐orbital calculations, fluorescence, cyclic voltammetry, photolysis, and electron‐spin‐resonance spin‐trapping techniques. Compared with 2, 2, 2‐trifluoroacetophenone, both photoinitiators exhibit larger redshift of the absorption spectra and higher molar‐extinction coefficients. PI‐Ben and PI‐Flu themselves can produce free radicals to initiate the polymerization of acrylate without any added hydrogen donor. These novel D‐π‐A type trifluoroacetophenone‐based photoinitiating systems exhibit good efficiencies (acrylate conversion = 48%–66%; epoxide conversion = 85%–95%; LEDs at 365–450 nm exposure) even in low‐concentration initiators (0.5%, w/w) and very low curing light intensities (1–2 mW cm −2 ). © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1945–1954 Abstract : Two novel D‐π‐A type trifluoroacetophenone‐based photoinitiators having biphenyl or fluorenyl conjugated systems were synthesized by Suzuki reactions. The obtained photoinitiators exhibited high UV‐Visible light sensitivity. Furthermore, two photoinitiators were soluble in common monomers of acrylate and epoxides. These results improved their applications in the radical and cationic photopolymerizations at 365 to 450 nm LEDs light sources even in low concentration initiators and weak exposure intensity, e.g., 1 to 2 mW cm −2 .